Manual de buenas prácticas de manufactura en empresa Tejada Trading y Cia S.A.S línea cosméticos (2019)
Due to the growing need of organizations to guarantee the quality of their products, Good Manufacturing Practices-BPM are born as a solution to this requirement. For the realization of the present monograph we worked in the collaboration of the company Tejada Trading & Cia SAS, who when wanting to venture into the market with their cosmetics line, saw the need to implement the BPM in order to ensure the quality of their products.